The librarians. Season one [videorecording (DVD)] - Rogers, John (Screenwriter) (Librarians, 2016)
This series centers on an ancient organization hidden beneath the Metropolitan Public Library dedicated to protecting an unknowing world from the secret, magical reality hidden all around. This group solves impossible mysteries, fights supernatural threats, and recovers powerful artifacts, including the Ark of the Covenant, the Spear of Destiny, and Excalibur.